2014
DOI: 10.1371/journal.pone.0109642
|View full text |Cite
|
Sign up to set email alerts
|

Amphibian Beta Diversity in the Brazilian Atlantic Forest: Contrasting the Roles of Historical Events and Contemporary Conditions at Different Spatial Scales

Abstract: Current patterns of biodiversity distribution result from a combination of historical and contemporary processes. Here, we compiled checklists of amphibian species to assess the roles of long-term climate stability (Quaternary oscillations), contemporary environmental gradients and geographical distance as determinants of change in amphibian taxonomic and phylogenetic composition in the Brazilian Atlantic Forest. We calculated beta diversity as both variation in species composition (CBD) and phylogenetic diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 61 publications
2
35
0
1
Order By: Relevance
“…We observed that at the largest spatial extent (SS4), species replacement was lower among the sites within the same region than among sites among the regions. Increasing the spatial extent usually includes biogeographical regions that have undergone different processes of speciation, extinction, and colonization, resulting in different regional species pools among the regions (Barton et al., ; da Silva et al., ; Comte et al., ; Qian & Ricklefs, ). Recently, da Silva et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed that at the largest spatial extent (SS4), species replacement was lower among the sites within the same region than among sites among the regions. Increasing the spatial extent usually includes biogeographical regions that have undergone different processes of speciation, extinction, and colonization, resulting in different regional species pools among the regions (Barton et al., ; da Silva et al., ; Comte et al., ; Qian & Ricklefs, ). Recently, da Silva et al.…”
Section: Discussionmentioning
confidence: 99%
“…Because regions contain different regional species pools (Vasconcelos et al., ), we predict that the values of species replacement will be lower among sites within the same region than among those of different regions. Therefore, we expect that the values of species replacement will be associated with the region in which sites are located due to environmental filters and/or dispersal limitations (da Silva, Almeida‐Neto, & Arena, ; da Silva, Almeida‐Neto, et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Entretanto, a distância geográfica não foi o principal fator, no qual as regiões mais próximas nem sempre foram as mais similares. Silva et al (2014) sugeriram que não somente os eventos atuais, como a distância geográfica, mas também os históricos, tais como condições topográficas, vegetação, limitação de dispersão, pontos de dispersão e isolamento geográfico, são possíveis formadores de comunidades. Além disso, as condições climáticas distintas entre regiões também podem restringir a dispersão de indivíduos que permanecem dentro da distribuição das espécies ancestrais (Wiens & Donoghue, 2004).…”
Section: Discussionunclassified
“…The distribution of organisms is the basis of ecological studies and can be determined by biotic and abiotic factors (Hutchinson, 1957;Soberón, 2007). For example, current patterns of species distributions are linked to historical and contemporary dispersals influenced by species characteristics and their specific functional traits (Baselga, Lobo, Svenning, Aragón, & Araújo, 2012;Carnaval, Hickerson, Haddad, Rodrigues, & Moritz, 2009;Carnaval & Moritz, 2008;Oberdorff, Hugueny, & Guegan, 1997;Ricklefs, 1987;Silva, Almeida-Neto, & Arena, 2014;Svenning & Skov, 2007).…”
Section: Introductionmentioning
confidence: 99%